Bioresorbable drug-eluting scaffolds for treatment of vascular disease. (3rd May 2016) - Suwannasom, Pannipa; Sotomi, Yohei; Tateishi, Hiroki; Tenekecioglu, Erhan; Zeng, Yaping; Kraak, Robin P.; Wykrzykowska, Joanna J.; De Winter, Robbert J.; Serruys, Patrick W.; Onuma, Yoshinobu
ABSTRACT: Introduction: Theoretical advantages of fully bioresorbable scaffold (BRS) stem from transient vessel support without rigid caging. Therefore, it could reduce long-term adverse events associated with the presence of foreign materials. Areas covered: This article will provide an overview of: drug-eluting BRS for various applications in the treatment of vascular disease; The mechanisms of active agent release from such scaffolds; currently available drug-eluting BRS and their future applications are also discussed. Expert opinion: The current BRS have been developed in order to achieve optimal vascular patency while providing long-term safety. The clinical efficacy and safety of BRS in coronary treatment have been reported as equal to that of the current metallic drug eluting stents in simple lesions. The application of BRS can potentially be expanded to other vascular beds. The research in bioengineering for the appropriate materials should not only focus on biocompatibility but also should be tailored according to the sites of implantation, which may require different strength and supporting period. The ultimate goal in this field is to develop a biocompatible device that provides equivalent and complementary therapy to other devices, and is able to disappear when the mechanical support and drug delivery are no longer required.